2019
DOI: 10.3389/fcell.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Signaling in the Liver – A Long and Ever-Expanding Story

Abstract: The first description of Hippo signaling in mammals a little more than 10 years ago showed a striking phenotype in the liver, linking the role of this signaling pathway to organ size control and carcinogenesis. Even though Hippo signaling has been extensively studied in the liver and other organs over the recent years, many open questions remain in our understanding of its role in hepatic physiology and disease. The functions of Hippo signaling extend well beyond cancer and organ size determination: components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 95 publications
5
52
0
1
Order By: Relevance
“…This study showed that C allele carriers in YAP1 rs11225163 are protected from HCC development in NASH. The hippo signaling seems to be the ideal candidate pathway that governs hepatocyte proliferation during regeneration [47]. Our results are in alignment with a recent report, which proved that progression HCC in NASH was attributed to YAP1 [48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that C allele carriers in YAP1 rs11225163 are protected from HCC development in NASH. The hippo signaling seems to be the ideal candidate pathway that governs hepatocyte proliferation during regeneration [47]. Our results are in alignment with a recent report, which proved that progression HCC in NASH was attributed to YAP1 [48].…”
Section: Discussionsupporting
confidence: 92%
“…However, this finding might indicate that YAP1 might lie at the intercept between severe advanced fibrosis/cirrhosis and HCC development in NASH. In agreement, previous studies showed that YAP activation in HSCs and hepatocytes could possibly increase carcinogenesis in cirrhotic livers [47,50]. However, a larger sample size is required to confirm this suggestion.…”
Section: Discussionsupporting
confidence: 90%
“…This pathway has only recently been implicated in the context of hepatic zonation, 29 with its main functionality being related to liver regeneration. 30 The central TF of the Hippo signaling pathway-YAP-is activated mostly in the periportal zone, 29 both in hepatocytes and cholangiocytes. This pattern appears conclusive, as liver regeneration has been implicated to occur through bilateral transdifferentiation between hepatocytes and cholangiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the influence of NPC in key signaling pathways relevant to LO formation, we performed a series of western blots (Fig. 4a) [23][24][25][26][27][28][29]. The protein activity analysis revealed that the III and IIP groups exhibited significantly lower activity of TGF-β (Fig.…”
Section: Discussionmentioning
confidence: 99%